Islamic Campus As An Agent Of Change, Transformative And Progressive: Kampus Islami Sebagai Agent Perubahan, Transormatif Dan Berkemajuan - Irokhmah, Islamiyatur; Mufdlilah, Mufdlilah; Suryaningsih, Endang Koni (Procedia of Social Sciences and Humanities, 2024)
Despite the pivotal role of Islamic universities, there remains a gap in understanding their transformative potential in addressing contemporary challenges exacerbated by globalization and modernization. Issues such as ethical enrichment alongside intellectual development pose challenges that require exploration.Existing literature highlights the dual challenge of balancing intellectual rigor with ethical enrichment within Islamic educational settings. However, specific insights into how Islamic campuses integrate these elements to foster transformative change remain underexplored.This study aims to explore the concept of Islamic campuses as transformative and progressive agents, focusing on their role in integrating Islamic values with modern knowledge and addressing societal challenges through education and community engagement.Findings from this literature-based research reveal that Islamic campuses, exemplified by Universitas 'Aisyiyah Yogyakarta, effectively integrate Islamic principles into their educational framework. Results indicate substantial progress in facilities such as mosques, libraries, and classrooms reflecting Islamic values, thereby enhancing the holistic development of students.This study contributes to understanding how Islamic campuses navigate the intersection of traditional Islamic teachings with contemporary educational demands, offering insights into their role as agents of ethical and intellectual transformation.The findings underscore the importance of integrating Islamic ethics with modern education, emphasizing the potential of Islamic campuses to foster socially responsible graduates equipped to address global challenges while upholding Islamic values